KECERDASAN INTERPERSONAL PESERTA DIDIK DI SEKOLAH DASAR - Ramdani, Jeni; Rohani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Interpersonal intelligence is a crucial aspect of student development, particularly at the elementary school level. This study aims to describe the interpersonal intelligence of elementary school students, including its definition, variations, supporting factors, and its role in social life and learning. This study employed a literature review method, analyzing three relevant scientific journals. The results indicate that interpersonal intelligence is an individual's ability to understand feelings and interact effectively with others. Interpersonal intelligence in elementary school students varies widely, including high, medium, and low. The development of this intelligence is influenced by several factors, including the family environment, school environment, and individual social experiences. Furthermore, interpersonal intelligence plays a crucial role in enhancing students' communication, cooperation, empathy, and conflict resolution skills. Therefore, the development of interpersonal intelligence requires attention from teachers and parents to support students' social and academic success.